2020
DOI: 10.1007/s11414-020-09686-5
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Evidence-Based Technical Assistance Model: a Process Evaluation of the National Training and Technical Assistance Center for Child, Youth, and Family Mental Health

Abstract: The National Training and Technical Assistance Center for Child, Youth, and Family Mental Health (NTTAC) supports the development and implementation of systems of care (SOC) for youth with serious emotional disorders (SED) and their families. This article presents results from a process evaluation of NTTAC, conducted to support the Center's quality improvement and contribute to the knowledge base around provision of technical assistance (TA). The evaluation used a mixed methods approach with data collection fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…This finding directly contradicts the results of the national study [ 14 ] of over 40 TA purveyors, which found that provision of basic and targeted TA surged after social distancing orders, and that intensive TA only accounted for 5% of all events. The New England ATTC’s ability to increase intensive TA offerings while other TA purveyors were providing predominantly basic or targeted support is noteworthy, especially given prior research indicating that long-term, ongoing TA is associated with better outcomes than one-shot, time-limited efforts [ 9 ]. Furthermore, research on high quality TA provision has suggested that intensive TA should provide frequent, ongoing opportunities for experiential learning [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding directly contradicts the results of the national study [ 14 ] of over 40 TA purveyors, which found that provision of basic and targeted TA surged after social distancing orders, and that intensive TA only accounted for 5% of all events. The New England ATTC’s ability to increase intensive TA offerings while other TA purveyors were providing predominantly basic or targeted support is noteworthy, especially given prior research indicating that long-term, ongoing TA is associated with better outcomes than one-shot, time-limited efforts [ 9 ]. Furthermore, research on high quality TA provision has suggested that intensive TA should provide frequent, ongoing opportunities for experiential learning [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Each regional ATTC works with expert trainers to provide three different levels of TA that vary in their objectives and duration: basic, targeted, and intensive [ 8 ]. TA is defined as a tailored approach to providing implementation support to, and increasing capacity for, continuous quality improvement [ 9 ]. Training is considered a discrete activity that can be included as part of any TA effort, guided by extensive evidence that training is insufficient for practice implementation and organizational change [ 10 ].…”
mentioning
confidence: 99%
“…The New England ATTC's ability to increase intensive TA offerings while other TA purveyors were providing predominantly basic or targeted support is noteworthy, especially given prior research indicating that long-term, ongoing TA is associated with better outcomes than one-shot, time-limited efforts (9). Furthermore, research on high quality TA provision has suggested that intensive TA should provide frequent, ongoing opportunities for experiential learning (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Each regional ATTC works with expert trainers to provide three different levels of TA that vary in their objectives and duration: basic, targeted, and intensive (8). TA is de ned as a tailored approach to providing implementation support to, and increasing capacity for, continuous quality improvement (9).…”
Section: Introductionmentioning
confidence: 99%
“…We know that early interventions are imperative and a number of the articles in this issue concentrate on youth, focusing on ways pediatric behavioral health services might intervene to reduce non-urgent emergency departments visits (in the Keefe et al paper), 1 developing training and technical assistance centers that respond to the special needs of youth with serious emotional disorders (in the Olson et al paper), 2 and assessing the mental health practices that have led to youth "aging out" of the system at 18 years (in the Cohen et al paper). 3 Additionally, we focus on the importance of diversity by highlighting the nature of mental health needs among an emerging Latino community with limited health care information (in the Bucay-Harari et al paper) 4 and examining how telepsychiatry might reduce treatment gaps in LGBT communities (in the Whaibeh et al paper).…”
mentioning
confidence: 99%